Effect of Priming on Vigor of Germinated Chili (Capsicum annum L.) Seeds in Aluminium Stress Conditions - Agustiansyah Agustiansyah; P. B. Timotiwu; E. Pramono; M. Maryeta (Politeknik Negeri Lampung., 2021)
Seed germination in ultisol is a problem. Ultisol has a low pH, poor in nutrients and organic matter, and high Al content. The low physiological quality of seeds is also a limiting factor. The purpose of this study was to determine the effect of priming on the seed vigor of two chili varieties whose seeds have expired and have not expired. This experiment consisted of 2 experiments, namely Experiment 1, which used seeds that had expired (deteriorating), and Experiment II, which used seeds that had not expired (non-deteriorating). This study was structured using a completely randomized design (CRD) which was repeated three times. This experiment is factorial. The first factor is priming, consisting of five levels: control, immersion in water, 30% PEG, 50 ppm GA3, and 1% KNO3. At the same time, the second factor in the first experiment was the seeds of the Tanjung 2 and Kencana varieties that had expired (deteriorating). In the second experiment, the second factor was the seeds of the Tanjung 2 and Kencana varieties that had not expired (non-deteriorating). The data obtained were analyzed using the R statistic program with a 5% HSD test. The results showed that priming with 50 ppm GA3 and 1% KNO3 increased the vigor of seeds that had expired (deteriorating). Meanwhile, priming with water and 1% KNO3 increased the vigor of seeds that had not yet expired (deterioration). The Kencana variety has a higher vigor than the Tanjung 2 variety on expired seeds. In seeds that have not yet expired, both varieties have the same good vigor.